ECAR Study of Faculty and Information Technology, 2014 (Educause Center for Applied Research (ECAR))
ECAR collaborated with 151 institutions to collect responses from 17,451 faculty respondents across 13 countries about their technology experiences.

(untitled) - Dahlstrom, Eden; Brooks, Christopher D. (2014)